1998
DOI: 10.1111/j.1528-1157.1998.tb01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression and Anxiety in Pediatric Epilepsy Patients

Abstract: Summary: Purpose:We assessed rates of symptoms of anxiety and depression among pediatric patients with epilepsy.Methods: We administered the Revised Child Manifest Anxiety Scale (RCMAS), and Child Depression Inventory (CDI) to 44 epilepsy patients aged 7-18 years (mean age 12.4 years). Demographic, socioeconomic, and epilepsy-related information was examined in relation to depression and anxiety scores.Results: No patients had been previously identified to have depression or anxiety. However, 26% had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
213
4
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(251 citation statements)
references
References 15 publications
17
213
4
17
Order By: Relevance
“…There are high rates of comorbid MDD and anxiety disorders in adults (28)(29)(30)(31)(32)(33) and children with epilepsy (34)(35)(36)(37)(38)(39)(40)(41). Amygdala volume findings, however, vary with two studies showing increased volumes in presurgical TLE adults with depression (42,43) and two studies showing no change in volumes in individuals with TLE (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…There are high rates of comorbid MDD and anxiety disorders in adults (28)(29)(30)(31)(32)(33) and children with epilepsy (34)(35)(36)(37)(38)(39)(40)(41). Amygdala volume findings, however, vary with two studies showing increased volumes in presurgical TLE adults with depression (42,43) and two studies showing no change in volumes in individuals with TLE (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…Ettinger et al 5 applied the quantitative scales Revised Child Manifest Anxiety Scale (RCMAS) 6 and Child Depression Inventory (CDI) 7 to assess depression and anxiety in a population of 44 children and adolescents ( from 7 to 18 years) with epilepsy and found that 26% of patients had increased depression scores and 16% had anxiety symptomatology.…”
mentioning
confidence: 99%
“…[19,51,55,56] Epilepsi ile ilişkili faktörler arasında tanımlanan antiepileptik ilaç çoklu tedavisinim de anksiyete bozukluğu riski ile ilişkili bulunmuştur. [19,50,51,56] Ancak antiepileptik ilaç politerapisinin direk bir risk faktörü olup olmadığı kesin olarak aydınlanmamıştır. Monoterapiye yanıtsız olguların daha şiddetli epilepsi düzeyinde olması ve artan epilepsi şidde-tinin anksiyete bozukluğu riski ile ilişkili olduğu da düşünülebilir.…”
Section: Risk Faktörleriunclassified